Research on the mechanism of high-efficiency milling cement plugs with low weight on bit and high rotational speed - Zirui Li; Feng Guan; Feng Wan; Haifeng Tian; Wang Liu (Journal of Petroleum Exploration and Production Technology, 2025)
Abstract With the continuous development of milling technology and the increasing number of slim hole plugging removal operations worldwide, how to guide operators to select reasonable working parameters to achieve efficient plugging removal has become a problem worth paying attention to. At present, the research on the optimization of working parameters based on the characteristics of plugging material is not complete. In order to explore the feasibility of efficient unplugging operation with low weight on bit and high rotational speed in slim hole, this paper chooses cement plug as plugging material, and uses Mechanical Specific Energy (MSE) and Rate of Penetration (ROP) as the evaluation index of plugging efficiency. A test bench was established and a low WOB milling test was designed. Meanwhile, a 3D simulation model of full-size PDC bit milling cement plug was established. Through the test and numerical simulation analysis, it is found that when the bit weight is enough to destroy the blockage, efficient operation can be realized under the working condition of low WOB and high rotational speed. A working parameter optimization method is proposed, and the recommended working interval is 3 kN WOB and 1500 ~ 2000 r/min rotational speed; 5 kN WOB, 1000 r/min rotational speed. The results show that the increase of WOB and rotational speed can improve the ROP of the bit, and it is feasible to use rotational speed to compensate the WOB to increase the ROP. In simulation and test, the efficiency of milling plugs is not good when the WOB is lower than 3 kN. To achieve high efficiency milling plugs, the priority should be to ensure that the WOB is enough to allow the cutter to normally break the plug. When analyzed with power drilling tools in conjunction with downhole motors, the ROP obtained by PDC bit with turbodrill under the condition of low WOB and high rotational speed is better than that obtained by a positive displacement motor with high WOB and low rotational speed, the results highlight the advantages of low WOB and high rotational speed milling cement plug. This paper provides a new idea for the optimization of working parameters of coiled tubing during plugging removal in slim holes.